Psychotherapy case formulation - Eells, Tracy D. (Theories of psychotherapy series., 2015)
APA offers the Theories of Psychotherapy Series as a focused resource for understanding the major theoretical models practiced by psychotherapists today. Each book presents a concentrated review of the history, key concepts, and application of a particular theoretical approach to the assessment, diagnosis, and treatment of clients. The series emphasizes solid theory and evidence-based practice, illustrated with rich case examples featuring diverse clients. Practitioners and students will look to these books as jewels of information and inspiration.